2023
DOI: 10.3390/foods12071557
|View full text |Cite
|
Sign up to set email alerts
|

Utilising Spent Tea Leaves Powder as Functional Ingredient to Enhance the Quality of Non-Gluten Shortbread Cookies

Abstract: The increasing prevalence of gluten-related disorders has led to higher consumer demand for convenient, gluten-free bakery products with health-promoting properties. In this study, non-gluten shortbread cookies were incorporated with various kinds of spent (green, oolong, and black) tea leaves powder (STLP) at 8% w/w. Cookies with STLP had significantly higher (p < 0.05) moisture (2.18–2.35%), crude fibre (14.5–14.9%), total dietary fibre (22.38–22.59%), insoluble dietary fibre (15.32–15.83%), soluble dieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Our results are comparable to those of Koh et al, who found that the tannin level of all the cookies made with spent tea powder was much higher than that of the control cookies. The high tannin content of the spent tea powder may be blamed for this.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Our results are comparable to those of Koh et al, who found that the tannin level of all the cookies made with spent tea powder was much higher than that of the control cookies. The high tannin content of the spent tea powder may be blamed for this.…”
Section: Resultssupporting
confidence: 90%
“…The heat breakdown of tannin during baking may be to blame for this . According to the findings, all of the cookies’ tannin concentration was within the allowed level for their antinutritional effect when consumed by humans …”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations